A Scalable, Ordered Scenario-Based Network Security Simulator - Yun, Joo Beom; Park, Eung Ki; Im, Eul Gyu; In, Hoh Peter (Systems Modeling and Simulation: Theory and Applications, 2005)
A network security simulator becomes more useful for the study on the cyber incidents and their defense mechanisms, as cyber terrors have been increasingly popular. Until now, network security simulations aim at damage estimation of incidents in small-size networks or performance analysis of information protection systems. However, a simulator is needed to handle large-size networks since attacks in these days are based on large-size global networks such as the Internet. The existing simulators have limitations for simulating large-scale Internet attacks. In this paper, a scalable, ordered scenario-based network security simulator is proposed. Our proposed simulator is implemented by expanding the SSFNet program to client-server architectures. A network security scenario is applied to test effectiveness of our proposed simulator.